Herramientas para adquisición de datos y modelación de la geometría del cordón en procesos de soldadura por arco eléctrico - Alvarez Bestard, Guillermo (2018)
Electric arc welding is widely used in industrial processes, but its automation is limited by the adverse environmental conditions in the periphery of the arc, which makes it difficult to measure the dimensions of the weld bead to close the control loop. Under these conditions, it is not possible to use conventional measuring systems. In this work, we describe a set of algorithms and hardware-software tools developed to obtain the data that allows to measure and estimate the geometry of the weld bead in this type of process. A data acquisition and open loop control system, a laser scanner and an algorithm to measure penetration using macrographic images of longitudinal cuts of the weld bead are developed. Most of these tools are characterized by their low cost, allowing their use in research and academic activities. The measurements are used to obtaining dynamic models of the weld bead geometry, using sensor fusion, in a conventional GMAW process with a constant voltage power source.